2019
DOI: 10.3390/nano9081111
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on Transition Metal Nitrides Nanoparticles as Heterogeneous Catalysts

Abstract: This short review aims at providing an overview of the most recent literature regarding transition metal nitrides (TMN) applied in heterogeneous catalysis. These materials have received renewed attention in the last decade due to its potential to substitute noble metals mainly in biomass and energy transformations, the decomposition of ammonia being one of the most studied reactions. The reactions considered in this review are limited to thermal catalysis. However the potential of these materials spreads to ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 79 publications
1
46
0
Order By: Relevance
“…Metal‐carbides due to their bonding between carbon atom and transition metal atom have unique properties such as high melting temperature (>3300 K), high hardness (>2000 kg/mm 2 ) and high tensile strength (>300 GPa) and show catalytic activity similar to activity of noble metals . Metal‐nitrides are characterized by two different effects: ligand effect and ensemble effect . Ligand effect results in changes in their electronic structure which strengthens adsorption of reactants and products similar to noble metals improving the selectivity of reaction.…”
Section: Current Understanding Of Co2 Catalytic Hydrogenationmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal‐carbides due to their bonding between carbon atom and transition metal atom have unique properties such as high melting temperature (>3300 K), high hardness (>2000 kg/mm 2 ) and high tensile strength (>300 GPa) and show catalytic activity similar to activity of noble metals . Metal‐nitrides are characterized by two different effects: ligand effect and ensemble effect . Ligand effect results in changes in their electronic structure which strengthens adsorption of reactants and products similar to noble metals improving the selectivity of reaction.…”
Section: Current Understanding Of Co2 Catalytic Hydrogenationmentioning
confidence: 99%
“…[45,46,50] Metal-nitrides are characterized by two different effects: ligand effect and ensemble effect. [51] Ligand effect results in changes in their electronic structure which strengthens adsorption of reactants and products similar to noble metals improving the selectivity of reaction. Ensemble effect decreases the number of available metal sites and results in creating of different adsorption sites.…”
Section: Current Understanding Of Co 2 Catalytic Hydrogenationmentioning
confidence: 99%
“…Furthermore, it has been reported that alkali promoters can improve the adsorption of CO2 to obtain alcohols or CO and the beneficial effect to higher alcohols followed the trend Cs > Rb > K > Na > Li [8]. Also, potassium has been used to keep the reduced phases of molybdenum in K-Mo2C/γ-Al2O3 system that was used in the reverse water gas shift reaction [9] and similar effects were observed for transition metal nitrides [10]. Potassium has also been successfully used as dopant in the Cu/ZnO system for which it seems that positively charged K can be the active site to adsorb the reactants.…”
Section: Introductionmentioning
confidence: 79%
“…19 Interstitial systems Unlike substitutional alloys, in order for the formation of interstitial alloys to occur the size of the foreign species needs to be sufficiently small in order to diffuse into the interstitial sites. The conventional interstitial alloys are metal hydrides 20 , carbides 21 , borides 22 and nitrides 23 , among others. These light elements, from the first period of the p-block and below, often have small atomic radii and dominant s-p orbitals, and often occupy the largest available interstitial site: the octahedral hole in face-centre-cubic (FCC) and hexagonal-close-packed (HCP) structures, and the trigonal prismatic hole in hexagonal structures.…”
Section: Substitution Systemsmentioning
confidence: 99%